Peningkatan Literasi Membaca Al-Quran Siswa Pemula Melalui Program Tilawah di Pondok Pesantren Perguruan Darulfunun El-Abbasiyah - Fatma Sari; Dandi Kurniawan; Abdullah A Afifi; Mona Eliza; Afifi Fauzi Abbas (IDRIS Darulfunun Institute, 2024)
As a center for learning about the Islamic religion, Pondok Pesantren is the best place to read and study the Quran, which is the main source and reference for Muslim behaviour. However, not all beginners who study religious knowledge at Pondok Pesantren have the ability and fluency to read the Quran. The location of this research is at the Pondok Pesantren Perguruan Darulfunun El-Abbasiyah, Limapuluh Kota Regency. This research is a report on the implementation of increasing Quran reading literacy with a recitation program for early students at the Tsanawiyah or Aliyah formal education level. Research on the implementation of this recitation program uses the DOE method, also using observation, interview and continuous evaluation techniques. Implementation is evaluated repeatedly against the targets achieved by students in each semester. The results of the implementation of this program show that the implementation of the recitation program is considered effective in increasing students' Quran reading literacy. This is because the application of the recitation program is very appropriate as an effort to speed up the fluency of reading the al-Quran for students who experience delays in reading the Al-Quran. This report is useful for the institution in particular and the development of Al-Quran reading skills for the entire community in general.